2018
DOI: 10.2495/eq180131
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Energy Recovery From Municipal Solid Waste in the Russian Federation

Abstract: Energy recovery from municipal solid waste (MSW) is currently a key factor in waste management in Russia, as can be seen from the corresponding changes in the state regulatory framework. The paper presents a comparative assessment of different waste flow characteristics; it focuses on pre-treatment options and the method of subsequent thermal treatment. It reflects the basic method of untreated MSW incineration and other advanced technologies which have different levels of waste preparation. Stepby-step resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…The heating system CO 2 emissions for districts emits an annual amount of 22.4 Mt CO 2 . Such emissions can be reduced by adopting renewable energy in running the heating system of the Moscow region [39].…”
Section: Energy System and Waste To Energy In Moscowmentioning
confidence: 99%
“…The heating system CO 2 emissions for districts emits an annual amount of 22.4 Mt CO 2 . Such emissions can be reduced by adopting renewable energy in running the heating system of the Moscow region [39].…”
Section: Energy System and Waste To Energy In Moscowmentioning
confidence: 99%
“…Scenario 4 (S4) is based on recovery and further use of the waste energy fraction (Polygalov et al, 2019). Excavated waste is sifted on a screen, and energy fractions of waste are collected at a sorting facility located next to the landfill site.…”
Section: Dimension 1 Landfill Mining Project Scenarios Based On Resou...mentioning
confidence: 99%
“…In a study in Irkutsk [43], an environmentally optimal scenario for waste management has been identified that includes the separate collection and processing of recyclable materials in combination with the preliminary aerobic mechanical and biological treatment of residual waste before disposal, but this scenario is not economically viable in real conditions. Energy recovery from waste is the most important factor in waste management in Russia, so it is important to investigate different waste flow characteristics [44]. The Russian Industrial development strategy for the processing, treatment and disposal of industrial waste and MSW for the period up to 2030 has defined one of the main CE resource-oriented indicator -the level of substitution (in percentage) of non-renewable natural resources for recycled ones for application in national economics, thus characterizing the scope of 3R (reduce-reuse-recycle) principle in the country [45].…”
Section: Russiamentioning
confidence: 99%